Micro Business Based Business Development in Tourist Village Case Study: Lembur Sawah Tourist Village, Bogor, Indonesia - Dian Sua Pratama, Bayu; Sobirov Baxtishodovich, Bobur (Journal of World Science, 2023)
Indonesia is a maritime and archipelagic nation-based country. No wonder Indonesia has many of the best tourist attractions. Indonesian tourism is one of the country's largest sources of foreign exchange, so the presence of Covid 19 has had a huge impact on Indonesia and several tourist areas in Indonesia such as Bali. However, the Indonesian government prepared a new strategy with a focus on developing tourist villages with the aim of popularizing ecotourism and improving the economy of the residents and succeeded in getting people in tourist villages to open micro businesses to simply prepare souvenirs for tourists. In the title above, we will find out some data on micro-enterprises in the village of Lembur Sawah and the impact of the tourism village on the village. This reaserch use qualitative, descriptive-analytical research; the data obtained is in the form of observation results, interview results, and field notes that have been collected. Lembur Sawah has formed a Tourism Mobilization Community that gathers people with the awareness and willingness to process and develop Mulyaharja into a tourist village; the tourism driving group is called "KOMPEPAR MULYAHARJA" and use a promotion mix, promotional objectives, promotional budgets, target visitors, promotional media used, sources of messages and feedback. Lembur Sawah is still very developed to increase visits so that increased visits will help community-owned micro-enterprises, even though they are still trying to organize training, attend exhibitions, and organize events to attract visitors to visit to Lembur Sawah.